Rolling Pampas agroecosystem : which landscape attributes are relevant for determining bird distributions? - Weyland, Federico (2014)
Fil: Weyland, Federico. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Recursos Naturales y Ambiente. Buenos Aires, Argentina.